2021
DOI: 10.3390/biomedicines9111660
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ferroptosis in Non-Alcoholic Fatty Liver Disease and Its Implications for Therapeutic Strategies

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become the chronic liver disease with the highest incidence throughout the world, but its pathogenesis has not been fully elucidated. Ferroptosis is a novel form of programmed cell death caused by iron-dependent lipid peroxidation. Abnormal iron metabolism, lipid peroxidation, and accumulation of polyunsaturated fatty acid phospholipids (PUFA-PLs) can all trigger ferroptosis. Emerging evidence indicates that ferroptosis plays a critical role in the pathological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 116 publications
0
38
0
1
Order By: Relevance
“…In that context, Nrf2 and GPx4 stand out as major protective mechanisms. 114,136 Overall, the results imply that the regulation of ferroptosis in the context of NAFLD is an intriguing notion that deserves further investigation.…”
Section: Ferroptosis In Nafldmentioning
confidence: 76%
“…In that context, Nrf2 and GPx4 stand out as major protective mechanisms. 114,136 Overall, the results imply that the regulation of ferroptosis in the context of NAFLD is an intriguing notion that deserves further investigation.…”
Section: Ferroptosis In Nafldmentioning
confidence: 76%
“…In this study, ferroptosis ( Figure 2F ), ROS metabolic process ( Figures 3A,B ), and NAFLD (containing IL-6, BID, PRKAA2) signaling were identified as the activated biological processes or pathways involved in CAVD, and particularly, NAFLD was validated by WebGestalt, DAVID, and Metascape, which was consistent with the previous findings ( 6 , 21 ). Iron overload was observed in patients with NAFLD and the liver damage could be attenuated by iron removal ( 22 , 23 ). Therefore, the pathological process of NAFLD is closely associated with ferroptosis due to iron overload and lipid peroxidation ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload was observed in patients with NAFLD and the liver damage could be attenuated by iron removal ( 22 , 23 ). Therefore, the pathological process of NAFLD is closely associated with ferroptosis due to iron overload and lipid peroxidation ( 23 ). In addition, it was shown that iron deposits and penetration of senescent erythrocytes into the lea?et fibrosa comprised a central component not only of the initiation but also of the progression of CAVD ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCD pathways mentioned above may be activated at different stages of NAFLD, and the key effector molecules involved are also the focus of attention when developing therapeutic agents for NAFLD. Therefore, targeting the modulation of the PCD pathway is an effective approach to prevent or treat NAFLD/NAFLD-HCC (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%